Efficacy and safety of etanercept in the treatment of sciatica: A systematic review and meta-analysis. (October 2017) - Jing, Shangfei; Yang, Chenyuan; Zhang, Xiaofei; Wen, Shuzheng; Li, Yuankui
Highlights: Etanercept treatment could significantly reduce pain in leg and back. ODI was not improved after the treatment of etanercept. Etanercept was recommended to treat sciatica with caution. Abstract: Etanercept might be promising to alleviate sciatica caused by lumbar disc herniation and spinal stenosis. However, the results remained controversial. We conducted a systematic review and meta-analysis to evaluate the efficacy of etanercept in patients with sciatica. PubMed, EMbase, Web of science, EBSCO, and Cochrane library databases were systematically searched. Randomized controlled trials (RCTs) and Controlled clinical trials (CCT) assessing the efficacy of etanercept on sciatica caused by lumbar disc herniation and spinal stenosis were included. Two investigators independently searched articles, extracted data, and assessed the quality of included studies. The primary outcome was leg pain scores. Meta-analysis was performed using random-effect model. Four RCTs and one CCT involving 184 patients were included in the meta-analysis. Overall, compared with placebo, etanercept could significantly reduce leg pain (Std. mean difference = −0.83; 95% CI = −1.59 to −0.06; P = 0.03) and back pain (Std. mean difference = −1.89; 95% CI = −3.34 to −0.43; P = 0.01). However, when comparing etanercept to steroids there was no significant difference in the relief of leg pain (Std. mean difference = −1.18; 95% CI = −3.21 to 0.84; P = 0.25) and back pain (Std. mean difference = −0.29; 95% CI = −1.26 to 0.67; P = 0.55). Etanercept showed no increase in Oswestry Disability Index (ODI) compared with placebo (Std. mean difference = −0.83; 95% CI = −2.03 to 0.37; P = 0.18) and steroids (Std. mean difference = −0.19; 95% CI = −1.15 to 0.77; P = 0.70). Etanercept treatment was associated with a significantly reduced pain in leg and back compared to placebo and may possibly improve leg pain relief compared to steroids, but failed to improve ODI. Etanercept should be recommended for sciatica with caution because of heterogeneity.